JAK2‐positive cutaneous myelofibrosis presenting as sclerosing extramedullary hematopoietic tumors on the scalp: case presentation and review of the literature. (6th August 2015) - LeBlanc, Robert E.; Lester, Laura; Kwong, Bernice; Rieger, Kerri E.
Abstract : We report the second case of cutaneous myelofibrosis with a documented JAK2 activating mutation involving the scalp of a 67‐year‐old woman with primary myelofibrosis in her marrow. In contrast to the previous case, the biopsy revealed extensive lesional collagen deposition and closely mimicked a fibrohistiocytic proliferation. Similar rare lesions occurring in the setting of myeloproliferative neoplasms have been called sclerosing extramedullary hematopoietic tumors. These entities appear histomorphologically and etiologically distinct from extramedullary hematopoiesis, and their diagnosis should prompt the workup for a myeloproliferative neoplasm in the absence of an antecedent diagnosis. The presence of the JAK2 mutation in our case confirmed that the lesions represented skin involvement by a neoplastic myeloid proliferation and not compensatory extramedullary hematopoiesis. Our patient died of disease several months following the appearance of her lesions, which is in keeping with other reports that suggest that cutaneous myelofibrosis may serve as an independent poor prognostic sign in otherwise advanced primary myelofibrosis. A review of the literature further emphasizes the importance of distinguishing this entity from mesenchymal neoplasms and acute myeloid leukemia involving the skin.